Design of Mobile Learning Content with a Mobile-Based Live Multimedia System - Izwan Amsyar; Haznah Latifah; Dewi Wuisan (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2022)
With the rise of world progress, information technology and telecommunications to the Internet have become a top priority. These advancements mark a watershed moment in mobile learning, or "mobile learning," as it is known (m-learning). M Learning has some extra learning capacity that can be accessed by anybody, at any time, from anywhere. The issues still exist in m-learning, including a shortage of hardware and platforms required by the system architecture and accessibility. In order to become comfortable for the user, a thorough examination of each component dealing with existing m-learning is also required. This research aims to address the problem by employing multimedia as a material that can provide more precise and detailed information. Multimedia m-learning services necessitate an internet connection, excellent access, and adequate hardware to benefit from the overall bias with good services provided by phones that offer mobile multimedia facilities. The study's primary goal is to create m-learning with multimedia services, and the expected results are a software-based content provider.